2008
DOI: 10.1080/14992020802033109
|View full text |Cite
|
Sign up to set email alerts
|

The choice of distracting task can affect the quality of auditory evoked potentials recorded for clinical assessment

Abstract: Auditory evoked potential (AEP) recordings often require subjects to ignore the stimuli and stay awake. In the present experiment, early (ABR), middle (MLR), and late latency (LLR) AEPs were recorded to compare the effect of five different distracting tasks: (1) doing nothing eyes open, (2) reading, (3) watching a movie, (4) solving a three-digit sum, and (5) doing nothing eyes closed (or counting the stimuli for LLR). Results showed that neither the amplitudes nor the latencies of the ABR, MLR, or LLR were af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…In contrast, children with ASD showed deficits in P1′ latency and peak-to-trough amplitude compared to TD children, but no additive effect of background noise, such that in this study, children with ASD processed speech in both quiet and noise comparably to the manner in which TD children encode speech in noise. Previous studies have investigated and dismissed the effect of video sounds on evoked potentials in the “quiet” condition (Lavoie et al 2008; McArthur et al 2003). However, given that children with ASD had quiet responses comparable to TD noise responses, it is possible that the soundtrack had a larger impact on the quiet responses of the children with ASD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, children with ASD showed deficits in P1′ latency and peak-to-trough amplitude compared to TD children, but no additive effect of background noise, such that in this study, children with ASD processed speech in both quiet and noise comparably to the manner in which TD children encode speech in noise. Previous studies have investigated and dismissed the effect of video sounds on evoked potentials in the “quiet” condition (Lavoie et al 2008; McArthur et al 2003). However, given that children with ASD had quiet responses comparable to TD noise responses, it is possible that the soundtrack had a larger impact on the quiet responses of the children with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Using this method, the children were able to listen to the movie soundtrack via the unoccluded, non-test ear. Although the video soundtrack is playing during the testing, we refer to this condition as “quiet” because masking of the sound-track is incomplete and is presented at <40 dB, a level known not to affect responses (Lavoie et al 2008; McArthur et al 2003). To further enhance compliance, children were accompanied by their parent(s) in the chamber and were permitted breaks during testing as needed.…”
Section: Methodsmentioning
confidence: 99%
“…Breaks were given when requested. Participants were seated watching a muted movie of their choice with active subtitles and were instructed to ignore the stimuli played [28, 29]. The sequence of stimulus presentation in a session was randomized.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous research findings have indicated the effects of attention on the exogenous N1 wave (see Horváth, , for review; see also Hillyard, Hink, Schwent, & Picton, ). Other early ERPs, such as P2 and the N1‐P2 complex, have also been associated with input processing‐related attention (Carretié, Martín‐Loeches, Hinojosa, & Mercado, ; Carretié, Mercado, Tapia, & Hinojosa, ; Huang & Luo, 2006; Lavoie, Hine, & Thornton, ; Morris et al., ; Nakahara & Ikeda, ; Weihing, Daniels, & Musiek, ). In the field of PTSD research, alterations in response to trauma‐related stimuli have also been observed in early ERP components such as N1 and P2 (Attias et al., ; Ehlers et al., ; Felmingham et al., ; Gjini et al., ; Klimova et al., ; Lewine et al., ; Metzger et al., ; Metzger, Pitman, Miller, Paige, & Orr, ).…”
Section: Discussionmentioning
confidence: 99%